2014
DOI: 10.1111/jan.12346
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and body image following treatment for early‐stage vulvar cancer: a qualitative study

Abstract: Findings from this study indicated that the majority of women experienced little to no long-term disruption to sexuality and body image following conservative treatment for early-stage vulvar cancer. Intimacy and relationship status were more closely linked to women's sexual satisfaction than physical arousal. Factors contributing to women experiencing negative emotions were radical vulvar excision, multiple vulvar procedures and/or the development of lymphoedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 42 publications
(60 reference statements)
1
37
0
1
Order By: Relevance
“…The results in our study further support the notion that, with the passage of time after surgery, psychosocial symptoms and issues (such as body image and sexuality) become more relevant for women with vulvar neoplasia (Janda et al 2004, Jefferies & Clifford 2012, Barlow et al 2014. In that phase especially, having a specific contact person to listen to their concerns and offer psychosocial support might be essential.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results in our study further support the notion that, with the passage of time after surgery, psychosocial symptoms and issues (such as body image and sexuality) become more relevant for women with vulvar neoplasia (Janda et al 2004, Jefferies & Clifford 2012, Barlow et al 2014. In that phase especially, having a specific contact person to listen to their concerns and offer psychosocial support might be essential.…”
Section: Discussionsupporting
confidence: 83%
“…, Jefferies & Clifford , Barlow et al . ). In that phase especially, having a specific contact person to listen to their concerns and offer psychosocial support might be essential.…”
Section: Discussionmentioning
confidence: 97%
“…Fear of anatomical changes related to surgery, fear of pain with intercourse, depression, worsening body image, and psychological distress have been reported in women undergoing vulvectomy for premalignant and malignant lesions [11, 64, 65]. Physical changes following surgery may include vaginal narrowing, numbness along the scar, removal of the clitoris, and change in tissue quality [64, 66, 67]. When compared to healthy controls, women undergoing vulvectomy have significantly more sexual dysfunction before and after surgery [65].…”
Section: Impact Of Gynecologic Cancer On Sexual Healthmentioning
confidence: 99%
“…Treatment is likely to be surgical intervention, ranging from local excision to radical vulvectomy including removal of the clitoris (Likes et al 2006). It is this treatment which can have significant negative psychological, emotional, sexual and physical effects on women of all ages (Barton & Barton 2003;Jeffries & Clifford 2011;Senn et al 2011), particularly in those cases where there has been radical vulvar excision, multiple vulvar procedures or where lymphoedema develops (Barlow et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life issues, in particular, have only recently received attention (Janda et al 2004(Janda et al , 2005. A literature review by Jeffries and Clifford in 2011, concluded that the few studies which had been published exhibited weaknesses in design and analytical methods (Barlow et al 2014). However, they were able to outline that there were key issues and challenges facing women with vulval can-cer relating to physical function, in particular, lower leg lymphoedema (see also Ryan et al 2003;Beesley et al 2007); psychological effects, such as depression and anxiety; impacts on sexual function, particularly among older women and when excision size was increased (Likes et al 2007); impacts on other relationships such as husbands or partners; and the quality and provision of information.…”
Section: Introductionmentioning
confidence: 99%